An approach to shipping information : evolutionary design using prototyping tool - Gupta, Sudhir; Overby, Magnus B.; Sadananda, Ramakoti; Oudheusden, Dirk L. van; The Government of Australia (Bangkok : Asian Institute of Technology, 1985)
Research Studies Project Report (M. Eng.) - Asian Institute of Technology, 1985
This research study aims to develop a shipping information system through a new system development methodology using Fourth Generation Languages of Prototyping tools. This system development methodology results in faster development of system, more user satisfaction and in a system which can easily be changed to meet the user's changing needs. The methodology combines the benefits of traditional development approach and the evolutionary approach to system design.
A Research Study submitted in partial fulfillment of the requirements for the degree of Master of Engineering, School of Engineering and Technology
Keywords: Information storage and retrieval systems -- Shipping